Workplace Violence and Patient Management Time in the Emergency Department: An Observational Study - Di Giorgio, Chiara; Cucchi, Isabella; Mendola, Marco; Costa, Maria Cristina; Tonelli, Fabio; Turchet, Elisa; Marrazzo, Matteo; Carrer, Paolo (La Medicina del Lavoro, 2025)
Background: Workplace violence is steadily rising, and the healthcare sector is one of the most impacted areas. Several studies have shown that patients’ long management times are a key factor in workplace violence in this setting. Objective: This study aims to analyze the prevalence and characteristics of aggressions against healthcare workers (HCWs) that occurred in 2023 in the Emergency Rooms (ER) of a large university hospital and to evaluate the potential relationship between the management time of a patient in the ER and the risk of violence incidents.Methods: To evaluate the prevalence and characteristics of aggressive events against HCWs that occurred in 2023, data from the “incident reporting” form were analyzed. Then, using the 2023 report on daily ER accesses, the management time of a patient at the ER was calculated. Finally, the average management times of patients on days when there were no aggressions were compared with those on days when there was one or more assaults against HCWs to evaluate the potential relationship between the average length of stay of a patient at the ER and the risk of aggression. Results: In 2023, 271 violent incidents were reported. Verbal aggressiveness was the most common (82.7%), and working the night shift was riskier (42.8%). In 36.2% of cases, patient management time was identified as a potential predictor of aggression. Other identified potential predictors included the patient and/or caregiver relationship with HCW (30.6%), the refusal to accept diagnostic-therapeutic protocols (27.3%), and the cultural background and temperamental traits of the patient or caregiver (18.8% and 11.8%, respectively). According to the logistic regression analysis, the likelihood of a violent incident during a 150-minute stay was less than 10%; it increased to 53% after 650 minutes. Conclusion: Workplace violence in healthcare settings results from a complex interaction of internal and external factors. Understanding how these elements interact and contribute to the development of incidents is essential for identifying key actions to reduce and mitigate violence.